PERENCANAAN KEUANGAN SYARIAH BAGI KELUARGA PADA DESA GUNUNG MALANG, KECAMATAN TENJOLAYA, KABUPATEN BOGOR - Trihantana, Rully; Mursyidah, Azizah; Kulsum, Umi (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
This community service activity discusses sharia financial planning for families in Gunung Malang Village, Tenjolaya District, Bogor Regency. This service aims to provide understanding and sharia financial planning to families in Gunung Malang Village, Tenjolaya District, Bogor Regency. This village was chosen because it has diverse economic conditions and a lack of understanding of sharia financial principles among the community. The method used is a transparent participation method for families regarding financial planning based on sharia principles. The result of this service is an increase in public understanding of the concepts and principles of sharia finance as well as the implementation of financial planning in accordance with sharia values ​​in everyday life. It is hoped that this service can provide positive benefits in improving the economic welfare and financial sustainability of families in Gunung Malang Village.